The quest for ghost gear in the German Baltic Sea: A team effort between WWF, divers, fisherfolk, and public authorities - Andrea Stolte; Gabriele Dederer; Jochen Lamp; Crayton Fenn; Mareen Lee; Wolfgang Frank; Christian Howe; Michael Günther; Heike Vesper; Stefanie Werner (Frontiers in Marine Science, 2022)
In this pilot project, World Wild Fund for Nature (WWF) Germany works together with regional divers, fisherfolk and public authorities to reduce the impact of lost fishing gear in the Baltic Sea. If not removed, ghost gear poses a threat to the marine environment and wildlife including seabirds, seals, harbour porpoises and fish. Over decades to centuries, lost fishing nets and ropes shed microplastic fibres into the marine environment. Removing this hazard reduces both the risk of entanglement as well as the contamination of the marine foodweb through ingestion of microplastics and associated chemicals. Identifying lost fishing gear in the marine environment poses one of the largest challenges impeding mitigation through gear retrieval operations. Lost gear can be drifting on the surface, in the water column, or can be sunken to the seafloor as a result of material composition, fouling, and entanglement. In the Baltic Sea, ghost gear is located on the seafloor and not visible during visual surface surveys from vessels. Identifying an efficient search methodology was therefore a key aspect of WWF’s ghost gear project. After trials with different search and retrieval methodologies, WWF Germany found sonar search technology to be the most efficient technique to locate lost gear on the seafloor. Sound waves avoid the limitations faced by divers or visual cameras in low-visibility environments, and a substantially larger area can be covered. In contrast to diving teams focussing on wreck retrievals, the many nets lost on the seafloor remain unnoticed by divers under most circumstances. A combination of sonar search providing exact GPS positions of suspect ghost gear, diver verification through the WWF Ghostdiver App, point-on retrievals with fishing vessels, and manual sorting for waste management provides an efficient methodology for long-term political implementation of regular lost gear retrieval campaigns.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Potential for exploitative competition, not intraguild predation, between invasive harlequin ladybirds and flowerbugs in urban parks - Andy G. Howe; Hans Peter Ravn; Christian Bressen Pipper; Alexandre Aebi (Biological Invasions, 2016)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Assessing S ymbiodinium diversity in scleractinian corals via next‐generation sequencing‐based genotyping of the ITS2 rDNA region - Chatchanit Arif; Camille Daniels; Till Bayer; Eulalia Banguera‐Hinestroza; Adrian Barbrook; Christopher J. Howe; Todd C. LaJeunesse; Christian R. Voolstra (Molecular Ecology, 2014)
The persistence of coral reef ecosystems relies on the symbiotic relationship between scleractinian corals and intracellular, photosynthetic dinoflagellates in the genus Symbiodinium . Genetic evidence indicates that these symbionts are biologically diverse and exhibit discrete patterns of environmental and host distribution. This makes the assessment of Symbiodinium diversity critical to understanding the symbiosis ecology of corals. Here, we applied pyrosequencing to the elucidation of Symbiodinium diversity via analysis of the internal transcribed spacer 2 ( ITS 2) region, a multicopy genetic marker commonly used to analyse Symbiodinium diversity. Replicated data generated from isoclonal Symbiodinium cultures showed that all genomes contained numerous, yet mostly rare, ITS 2 sequence variants. Pyrosequencing data were consistent with more traditional denaturing gradient gel electrophoresis ( DGGE ) approaches to the screening of ITS 2 PCR amplifications, where the most common sequences appeared as the most intense bands. Further, we developed an operational taxonomic unit ( OTU )‐based pipeline for Symbiodinium ITS 2 diversity typing to provisionally resolve ecologically discrete entities from intragenomic variation. A genetic distance cut‐off of 0.03 collapsed intragenomic ITS 2 variants of isoclonal cultures into single OTU s. When applied to the analysis of field‐collected coral samples, our analyses confirm that much of the commonly observed Symbiodinium ITS 2 diversity can be attributed to intragenomic variation. We conclude that by analysing Symbiodinium populations in an OTU ‐based framework, we can improve objectivity, comparability and simplicity when assessing ITS 2 diversity in field‐based studies.